Identity Politics' Issue In Indonesia Presidential Election 2019 - Ida Susilowati; Zahrotunnimah Zahrotunnimah; Nur Rohim Yunus (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
AbstractPresidential Election in 2019 has become the most interesting executive election throughout Indonesia's political history. People likely separated, either Jokowi’s or Prabowo’s stronghold. Then it can be assumed, when someone, not a Jokowi’s stronghold he or she certainly within Prabowo’s stronghold. The issue that was brought up in the presidential election campaign, sensitively related to religion, communist ideology, China’s employer, and any other issues. On the other side, politics identity also enlivened the presidential election’s campaign in 2019. Normative Yuridis method used in this research, which was supported by primary and secondary data sourced from either literature and social phenomenon sources as well. The research analysis concluded that political identity has become a part of the political campaign in Indonesia as well as in other countries. The differences came as the inevitability that should not be avoided but should be faced wisely. Finally, it must be distinguished between political identity with the politicization of identity clearly.Keywords. Identity Politics, 2019 Presidential Election